Social Media Influencers: Expectations vs Reality in Traveling - Feronica Simanjorang (LifeSciFi, 2024)
Social media influencers are an effective marketing instrument on social media. This research looks at how social media influencers build audience expectations through the content they are sharing, to the reality that audiences get as tourists. This research used an explanatory qualitative method and conducted in-depth interviews with 20 interviewees to get primary data. The researcher observed that social media influencers are used by the tourism sector in Lake Toba to promote tourism destinations by inviting influencers to attract audiences to visit by expecting the same experience when viewing the influencers' content. The results of this study indicate that the role of influencers is very important to promote tourism destinations and help to direct and provide information to the audience from the travel experiences shared by them so as to influence the perception, interest in visiting, and travel decisions of tourists.